Preservation of the Klana Udeng Mask Dance at the Mulya Bhakti Studio in Indramayu - Johan, Yuremia (Jurnal Seni Tari, 2024)
The Klana Udeng Mask Dance is a dance created by the development of the Babangan mask in Indramayu. This dance is one of the materials taught by Sanggar Mulya Bhakti led by Wangi Indriya for beginner dancers, both teenagers and children. This research will examine conservation with three main questions, namely who is preserving, what is being preserved, and how conservation is carried out. To answer this problem, Raymond Williams' Sociology-Culture theory is used which consists of three main components, namely institutions, content, and effect. Institutions (cultural institutions) ask who is involved in preserving the culture. Content (cultural content) asks what is produced and what values ​​are expected, then effect (cultural norms) asks how preservation efforts are carried out. The research method used is a qualitative descriptive-analytical method, namely research whose aim is to describe and analyze the object being studied as it is, as well as provide systematic, factual, and accurate reasons regarding the facts of the object being studied so that it can be analyzed according to the circumstances. Cultural institutions are the Mulya Bhakti studio, the community, and the government. Cultural content produces tangible and intangible values, and cultural norms produce a cultural identity that is characteristic of the Klana Udeng Dance and other mask performances.